2010
DOI: 10.1039/b926992d
|View full text |Cite
|
Sign up to set email alerts
|

Mean-field models of structure and dispersion of polymer-nanoparticle mixtures

Abstract: We review some recent research developments in coarse-grained modeling based on mean-field approaches of the equilibrium dispersion and structure of polymer nanoparticle composites. We focus on three issues: (i) dispersion and phase behavior of particles in homopolymer matrices; (ii) dispersion in mixtures of homopolymers with grafted nanoparticles; (iii) self-assembly and organization of nanoparticles in block copolymer matrices. In each of these topics, we highlight that the dispersability and the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 176 publications
(293 reference statements)
2
76
0
Order By: Relevance
“…9, which is significantly larger, simply because the latter is the result of integrated pair correlation functions and incorporates long range density fluctuations in surrounding "shells". It has been previously suggested that many-body effects may be responsible for increased immiscibility of smaller colloids due to overlapping many-bodied polymer depletion layers [22,23], however in this work we posit that many-body depletion on a monomeric level is a more satisfactory explanation, given that in the protein limit, polymeric depletion effects are felt at distances on the order of the polymer mesh's correlation length which is much smaller than the polymer's overall dimensions. This is supported by the observation that the locations of structural features collapse only when the abscissa is linearly shifted by the monomer diameter (reduced distance, l), suggesting that there is an underlying effect at this length scale.…”
Section: Than 1 K B T Along the Opposite Branch (Open Symbols)mentioning
confidence: 41%
See 1 more Smart Citation
“…9, which is significantly larger, simply because the latter is the result of integrated pair correlation functions and incorporates long range density fluctuations in surrounding "shells". It has been previously suggested that many-body effects may be responsible for increased immiscibility of smaller colloids due to overlapping many-bodied polymer depletion layers [22,23], however in this work we posit that many-body depletion on a monomeric level is a more satisfactory explanation, given that in the protein limit, polymeric depletion effects are felt at distances on the order of the polymer mesh's correlation length which is much smaller than the polymer's overall dimensions. This is supported by the observation that the locations of structural features collapse only when the abscissa is linearly shifted by the monomer diameter (reduced distance, l), suggesting that there is an underlying effect at this length scale.…”
Section: Than 1 K B T Along the Opposite Branch (Open Symbols)mentioning
confidence: 41%
“…These clearly showed that for athermal systems with monomer-monomer excluded volumes, critical densities for d < 0.25 collapse to a uniform master curve under rescaling arguments; however, for d ≥ 0.25 at identical q r , the solutions start demixing at much lower concentrations. McMillan-Mayer-type approaches have suggested this may be due to many-body effects [22,23], but to our knowledge simulations supporting this claim have not yet been performed in the protein limit. In Ref.…”
mentioning
confidence: 89%
“…Mechanisms of controlling the state of particle aggregation in these complex mixtures remain elusive and poorly understood [6]. Conceptual frameworks for achieving good dispersion generally rely on chemically or physically bound polymer layers [7,8] to induce a repulsive interparticle potential of mean force between nanoparticles [9,10]. Nonetheless, understanding the nature of, and what controls, the structure and properties of these layers remains an outstanding challenge in soft matter of broad importance in polymer science, colloid science, and even biological systems.…”
mentioning
confidence: 99%
“…Many reviews for various aspects of BCP nanocomposites have been published [4,5,8,12,15,16,18,19,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. To this end, considerable progress has been made in selectively controlling the distribution and location of QD/NP into the desired BCP domains [5,12,16,24,32,42,43].…”
Section: Introductionmentioning
confidence: 99%